FTIR and XRD evaluation of magnesium doped hydroxyapatitesodium alginate powder by precipitation method - Kanasan, Nanthini; Adzila, S.; Rahman, H. A.; Bano, Nazia; Panerselvan, G. (Trans Tech Publications, 2018)
Composites material were developed to acquire the desired material properties for biomedical applications in the recovery of defect bone by using Mg-doped HA/SA. Hydroxyapatite (HA) is the major constituent and essential component in bone and teeth. The stability of Mg-doped HA/SA is influenced by starting precursor powders, preparation condition and method of preparing the samples for implant materials. The precipitation method was employed to prepare Mg-doped HA/SA powders by varying the composition of Mg at temperature 1300°C. The influence of Mg-doped HA/SA on phase composition, chemical structure and a functional group at various weight percentages (0.5wt%-1.5wt %) were accomplished through X-ray diffraction (XRD) and Fourier Transform Infrared Spectroscopy (FTIR) analyses. Based on the XRD and FTIR analyses, there is the presence of different peaks intensity and adsorption bands which indicates the shifted of peaks due to the doping process and a chemical interaction were observed between the inorganic and organic phase. Furthermore, the transformation of β-TCP due to increase in sintering temperatures are caused by the presence of magnesium ions. The OHstretching bands of HA/SA are traced by FTIR that identified the decomposition of Mg-doped HA/SA.